2019
DOI: 10.1111/1749-4877.12341
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature, activity patterns and hunting in free‐living cheetah: biologging reveals new insights

Abstract: As one of the few felids that is predominantly diurnal, cheetahs (Acinonyx jubatus Von Schreber, 1775) can be exposed to high heat loads in their natural habitat. Little is known about long-term patterns of body temperature and activity (including hunting) in cheetahs because long-term concurrent measurements of body temperature and activity never have been reported for cheetahs, or indeed for any free-living felid. We report here body temperature and locomotor activity measured with implanted data loggers ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 53 publications
(81 reference statements)
3
18
1
Order By: Relevance
“…Here, we suggest that the behavioural ecology of a medium sized carnivore in the arid zone is driven by limitations to heat dissipation regardless of season, in line with the hypothesis that heat dissipation limits the upper boundary of total energy expenditure [22]. The shifts in behaviour observed in this study in response to increasing ambient temperatures have also been reported for other arid zone carnivores, such as Namibian cheetahs (Acinonyx jubatus) and African wild-dogs (Lycaon pictus) [62,63]. Given the previously reported physiological capacity of dingoes to acclimate to temperatures exceeding 40°C within months [33], alongside evidence of behavioural thermoregulation reported here, it appears that dingoes may be equipped to survive a predicted increase in temperatures in their environment, albeit via behavioural shifts.…”
Section: Discussionsupporting
confidence: 87%
“…Here, we suggest that the behavioural ecology of a medium sized carnivore in the arid zone is driven by limitations to heat dissipation regardless of season, in line with the hypothesis that heat dissipation limits the upper boundary of total energy expenditure [22]. The shifts in behaviour observed in this study in response to increasing ambient temperatures have also been reported for other arid zone carnivores, such as Namibian cheetahs (Acinonyx jubatus) and African wild-dogs (Lycaon pictus) [62,63]. Given the previously reported physiological capacity of dingoes to acclimate to temperatures exceeding 40°C within months [33], alongside evidence of behavioural thermoregulation reported here, it appears that dingoes may be equipped to survive a predicted increase in temperatures in their environment, albeit via behavioural shifts.…”
Section: Discussionsupporting
confidence: 87%
“…Establishing the true frequency of encounters between predators and prey requires locations to be recorded more frequently than hourly, because much ground can be covered by both predator and prey during the dynamics of the interaction. Accelerometers could help document the specific movements of both interactors during a hunt, successful or otherwise (Wilson et al 2018, Hetem et al 2019. Kills can be inferred from subsequent lack of movement by the predator, provided that the carcass takes several hours to consume (Davidson et al 2012).…”
Section: Gaps In Knowledgementioning
confidence: 99%
“…English pointer dogs show no obvious loss in hunting performance during days that are particularly hot and humid (Davenport, Kelley, Altom, & Lepine, 2001). Horses, swine, goats and sled dogs can tolerate their core body temperatures reaching 42 • C (Armstrong, Delp, Goljan, & Laughlin, 1987;Caputa, Feistkorn, & Jessen, 1986;Hodgson et al, 1993;Marlin et al, 1996;McConaghy, Hales, Rose, & Hodgson, 1995;Phillips, Coppinger, & Schimel, 1981;Poole & Erickson 2011), and both cheetah (Hetem et al, 2013(Hetem et al, , 2019 and African wild dogs (Taylor, Schmidt-Nielsen, Dmi'el, & Fedak, 1971) have been recorded in the wild with core temperatures over 41 • C, although this is uncommon.…”
Section: New Findingsmentioning
confidence: 99%
“…English pointer dogs show no obvious loss in hunting performance during days that are particularly hot and humid (Davenport, Kelley, Altom, & Lepine, 2001). Horses, swine, goats and sled dogs can tolerate their core body temperatures reaching 42°C (Armstrong, Delp, Goljan, & Laughlin, 1987; Caputa, Feistkorn, & Jessen, 1986; Hodgson et al., 1993; Marlin et al., 1996; McConaghy, Hales, Rose, & Hodgson, 1995; Phillips, Coppinger, & Schimel, 1981; Poole & Erickson 2011), and both cheetah (Hetem et al., 2013, 2019) and African wild dogs (Taylor, Schmidt‐Nielsen, Dmi'el, & Fedak, 1971) have been recorded in the wild with core temperatures over 41°C, although this is uncommon. In comparison, human distance runners and cyclists rarely attain core temperatures above 40°C (hyperpyrexia) even in high ambient temperatures (Laursen et al., 2006; Figures 3 and 4 of Nybo & González‐Alonso 2015; Williams, Wickes, Gilmour, Barker, & Scott, 2014;Valentino, Stuempfle, Kern, & Hoffman, 2016), and heat stress resulting in failure to complete races (i.e.…”
Section: Introductionmentioning
confidence: 99%